Minute mysteries 2 : more stories to solve - Witkowski, Teri.; Hirsch, Jennifer; Andreasen, Dan. (Middleton, WI. : Pleasant Co., 2007)
Characters from the American Girl books are featured in eleven short stories with mysteries, puzzles, and riddles for the reader to solve.
"American girl."
Keywords: Detective and mystery stories, American; Children's stories, American; Mystery and detective stories; Short stories